Preparation of herbal ointments by the method of crushing the flowers - BELLACHE, Rebiha (Biopolymer Applications Journal, 2023)
The present work aims to elaborate the ointments prepared by the method of grinding the flowers of plant calendula arvensis and dandelion. The subject has been reinforced by characterizations namely physical analysis by measuring pH, conductivity and water resistance test, chemical analysis by infrared spectroscopy and morphological analysis (visually and microscopically). From the results, we noticed that in the macroscopic characterization, a semi-solid consistency and homogeneity for the two ointments prepared by the method of grinding the flowers of two plants: calendula arvensis and Dandelion. Microscopically, the both ointments (CAO and DO) have a better physical stability; the latter is characterized by a homogeneous appearance, which was obtained. The yellow flowers ointment DO shows a better chemical stability than the CAO orange flower by the presence of increase of intensity in all the characteristic bands, which confirmed by FTIR analysis, finally, both ointments are water resistant, which was confirmed by the test of water resistance .